Stay or go? Space and resource use of the great hammerhead (Sphyrna mokarran) off Andros Island, The Bahamas - Guttridge, T. L.; Heim, V.; Dedman, S.; Guttridge, A. E.; Bain, S. A.; Keller, B. A.; Matich, P. (Frontiers in Marine Science, 2025)
In light of global declines of upper-level marine predators, such as the great hammerhead, (Sphyrna mokarran) a thorough understanding of their behavioral ecology is needed for designing effective management strategies to preserve their key role in maintaining ecosystem functioning, stability, and resilience. Within the northwestern Atlantic, great hammerheads display regional connectivity between the U.S. East Coast and the western edge of The Bahamas, but despite the suggested importance of the Bahamian shark sanctuary towards regional population recovery strategies, relatively few data exist from other areas of The Bahamas. This study used fisheries-independent drumline captures, satellite telemetry, and bulk stable isotope analysis to advance our understanding of the residency, space use, and trophic role of great hammerheads in Andros, the largest island in The Bahamas. We examined movement behaviors and thermal range within the Bahamian Exclusive Economic Zone, and constructed Bayesian mixing models based on carbon, nitrogen, and sulfur isotope ratios to estimate the importance of prey species in the diet of great hammerheads. Our data revealed year-round residency of Andros-caught great hammerheads in Bahamian waters with site-fidelity to and high use of habitats along the reef-drop off and flats of Andros. Great hammerheads predominantly fed on barracuda and small-bodied elasmobranchs in Andros connecting food webs from the pelagic zone to the shoreline. This study expands our knowledge of the ecology of great hammerheads in the northwestern Atlantic and shows that, despite their highly-mobile nature, some individuals reside in the Bahamas year round. These findings suggest the Bahamian shark sanctuary could be more than just a seasonal refuge for this species as previously proposed, and merit further research to assess the conservation value of the sanctuary towards regional rebuilding goals for greathammerheads.